IV Thrombolysis with or without endovascular treatment for suspected ischemic stroke in patients with intracranial tumors - Seystahl, Katharina Gertrud; Martinez-Majander, Nicolas; Salerno, Alexander; Beyeler, Morin; Erdur, Hebun; Marto, João Pedro; Hametner, Christian; Zedde, Marialuisa; Pezzini, Alessandro; Leker, Ronen; Altersberger, Valerian; Costamagna, Gianluca; et al. (Neurology, 2023)
Background and Objectives: IV thrombolysis (IVT) for suspected ischemic stroke in patients with intracranial neoplasms is off-label. However, data on risks of intracranial hemorrhage (ICH) are scarce. - Methods: In a multicenter registry-based analysis within the European Thrombolysis in Ischemic Stroke Patients (TRISP) collaboration, we assessed frequencies of symptomatic and fatal ICH after IVT for suspected ischemic stroke in patients with intracranial tumors by descriptive statistics and analyzed associations with clinical and imaging characteristics by binary logistic regression. Definition of symptomatic ICH was based on the clinical criteria of the European Cooperative Acute Stroke-II trial including hemorrhage at any site in cranial imaging and concurrent clinical deterioration. - Results: Screening data of 21,289 patients from 14 centers, we identified 105 patients receiving IVT; among them were 29 patients (28%) with additional endovascular treatment, with suspected, that is, imaging-based, or histologically confirmed diagnosis of intracranial tumors. Among 104 patients with CT or MRI after IVT available, symptomatic and fatal ICH were observed in 9 and 4 patients (9% and 4%, respectively). Among 82 patients with suspected or confirmed meningioma, symptomatic and fatal ICH occurred in 6 and 3 patients (7% and 4%), respectively. In 18 patients with intra-axial suspected or confirmed primary or secondary brain tumors, there was 1 symptomatic nonfatal ICH (6%). Of 4 patients with tumors of the pituitary region, 2 patients (50%) had symptomatic ICH including 1 fatal ICH (25%). Tumor size was not associated with the occurrence of symptomatic ICH (odds ratio 2.8, 95% CI 0.3-24.8, p = 0.34). - Discussion: In our dataset from routine clinical care, we provide insights on the safety of IVT for suspected ischemic stroke in patients with intracranial tumors, a population that is commonly withheld thrombolysis in clinical practice and prospective trials. Except for a potential high risk of symptomatic ICH after IVT in patients with tumors of the pituitary region, frequencies of symptomatic ICH in patients with intracranial tumors in our cohort seem to be in the upper range of rates observed in previous studies within the TRISP cooperation. These results may guide individual treatment decisions in patients with acute stroke and intracranial tumors with potential benefit of IVT.